SOSIALISASI SISTEMATIKA PENYUSUNAN DAN SUBSTANSI MATERI PERATURAN DESA DI DESA WAWORAHA KECAMATAN SOROPIA KABUPATEN KONAWE - Heryanti, Heryanti; Intan, Nur; Ukkas, Jumiati; Tabiu, Ramadan; Sulihin, La Ode Muhammad; Syukri, Muhammad; Aliansa, Wahyu (Universitas Halu Oleo, 2024)
Village regulations have a function as one of the formal foundations for the implementation of village government and a means of dealing with legal problems in society, but not all elements of village government understand the preparation procedures and material substance that can be contained in village regulations. It is not uncommon for village communities to not know their role in the process of drafting village regulations. The aim of this activity is to increase the community's knowledge and understanding of the systematic preparation and substance of Village Regulation material, improve the quality of drafting village regulations in accordance with the mechanisms and principles for the formation of statutory regulations, and increase community legal awareness regarding the urgency of the existence of Village Regulations for the benefit and improvement of welfare. villagers. Preparation for activities starts from determining the location to identifying legal problems in the community and then preparing outreach materials. The activity was carried out using a lecture method to the participants which was then followed by questions and answers. The activity was carried out by the community service team from the university involving students. The results of the activity were that it was very important for village government officials to involve the community to understand the systematics and substance of drafting village regulations. The preparation of good village regulations with understanding from all parties is one of the benchmarks for the smooth implementation of village government.